Organisation of Work of a Speech Therapist in an Educational Institution under Martial Law - Korol, Alyona (Pedagogical Discourse, 2025)
The article examines the process of organizing the work of a speech therapist in educational institutions under martial law, as well as specific aspects, forms and methods of this work. The author used the methods of analysis of scientific and methodological literature and normative legal acts, synthesis, comparison, and generalization. In the context of martial law, the functioning of the education system faces unprecedented challenges, which requires the adaptation of traditional approaches to the provision of correctional and developmental services, including speech therapy. Children who have experienced traumatic events and have undergone changes in their normal life often demonstrate a deterioration in speech development and need special support. This necessitates a deeper understanding and optimization of the organization of speech therapist’s work in modern conditions. The article analyzes the peculiarities of organizing the work of a speech therapist in an educational institution under martial law. The main challenges and problems faced by speech therapists in these conditions are summarized, including security risks, adaptation to distance and blended learning formats, the psychological state of participants in the educational process and limited resources. The adapted forms and methods of speech therapy work, including the use of distance technologies, work in shelters and the organization of inclusive education in the conditions of displacement are revealed. The specifics of diagnostic and correctional work with children who have experienced traumatic events are analyzed. Recommendations for psychological support and prevention of professional burnout of speech therapists are generalized. The ways to improve the interaction of a speech therapist with parents, teachers and other professionals to ensure holistic support for children are revealed. The importance of interdepartmental cooperation for the effective organization of speech therapy is analyzed. The scientific novelty of the article lies in the systematic analysis of the experience of speech therapists in martial law, generalization of key problems and disclosure of new approaches to the organization of speech therapy adapted to modern realities.